The Role of the Rodent Insula in Anxiety - Méndez-Ruette, Maxs; Linsambarth, Sergio; Moraga-Amaro, Rodrigo; Quintana-Donoso, Daisy; Méndez, Luis; Tamburini, Giovanni; Cornejo, Francisca; Torres, Rodrigo F.; Stehberg, Jimmy (Frontiers in Physiology, 2019)
The human insula has been consistently reported to be overactivated in all anxiety disorders, activation which has been suggested to be proportional to the level of anxiety and shown to decrease with effective anxiolytic treatment. Nonetheless, studies evaluating the direct role of the insula in anxiety are lacking. Here we set out to investigate the role of the rodent insula in anxiety by either inactivating different insular regions via microinjections of glutamatergic AMPA receptor antagonist CNQX or activating them by microinjection of GABA receptor antagonist bicuculline in rats, before measuring anxiety-like behavior using the elevated plus maze. Inactivation of caudal and medial insular regions induced anxiogenic effects, while their activation induced anxiolytic effects. In contrast, inactivation of more rostral areas induced anxiolytic effects and their activation, anxiogenic effects. These results suggest that the insula in the rat has a role in the modulation of anxiety-like behavior in rats, showing regional differences; rostral regions have an anxiogenic role, while medial and caudal regions have an anxiolytic role, with a transition area around bregma +0.5. The present study suggests that the insula has a direct role in anxiety.